Copper oxide / tungsten oxide composite material, preparation method thereof and application of copper oxide / tungsten oxide composite material in gas sensor
By preparing WO3 snowflake nanoplate and compositeing CuO on its surface, CuO/WO3 composite material is formed, which solves the problems of low response value, long recovery time and poor selectivity of the acetylacetone sensor, high sensitivity, fast response and stability are achieved, reducing the operating temperature, and improving the safety and applicability of the sensor.
Patent Information
- Application Number
- CN202510575613.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-06
- Publication Date
- 2025-08-05
AI Technical Summary
The existing acetylacetone sensor has low response value, long response recovery time and poor selectivity, and has a burn/explosion risk, making it difficult to meet the actual application needs.
By preparing WO3 snowflake-shaped nanoplate and compositeing CuO on its surface, CuO/WO3 composite material was formed. The composite material was synthesized by a simple hydrothermal method to optimize its gas-sensitive properties.
It realizes high sensitivity, high selectivity and rapid response recovery to acetylacetone gas, reduces operating temperature, improves the stability and safety of the sensor, and meets practical application needs.
Smart Images

Figure CN120423602A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of gas detection, and in particular to a copper oxide / tungsten oxide composite material, a preparation method thereof, and an application thereof in a gas sensor. Background Art
[0002] With the development of global industry, people are increasingly concerned about their living environment and their health. Consequently, the field of gas sensing has experienced rapid growth in recent years. Acetylacetone is a common chemical raw material and organic intermediate. Its solutions and vapors are prone to combustion when exposed to heat, open flames, or strong oxidants. They can irritate mucous membranes and skin, causing symptoms such as headaches, nausea, and suffocation. They also pose a significant risk to the environment and atmosphere. Therefore, developing an inexpensive gas sensor that can efficiently detect acetylacetone is of great significance, both for human health and environmental protection.
[0003] WO3 is an important inorganic transition metal oxide and a typical n-type semiconductor material with a band gap of approximately 2.4-2.8eV. It has attracted widespread attention from scientists at home and abroad due to its good thermal stability, low cost and low toxicity. Many studies have shown that WO3 has good gas sensitivity. However, pure WO3 sensors often have disadvantages such as low response value, long response recovery time and poor selectivity, which make it difficult to meet market demand. Appropriate modification of WO3 can well solve these problems, such as constructing a pn heterojunction.
[0004] Currently, there are very few acetylacetone sensors. Liu et al. used Zn(NO3)2·6H2O and GO to synthesize ZnO ultrathin nanosheets under hydrothermal conditions. The response / recovery time to 100 ppm of acetylacetone gas at 340°C was 19 / 94s. The complex synthesis method and long response recovery time seriously limit the practical application of the sensor. Moreover, for flammable gases such as acetylacetone, the higher operating temperature will also increase the risk of combustion / explosion during the use of the sensor.
[0005] Therefore, the present invention provides a new method for synthesizing WO3 snowflake-shaped nanoplates, and by compounding a small amount of CuO on the surface of WO3, the composite material has excellent gas-sensing performance to acetylacetone. Summary of the Invention
[0006] The purpose of the present invention is to provide a WO3 snowflake-shaped nanoplate and a preparation method thereof in view of the technical defects existing in the prior art.
[0007] Another object of the present invention is to provide a CuO / WO3 composite material based on the WO3 snowflake-shaped nanoplate and a preparation method thereof.
[0008] Another object of the present invention is to provide application of the CuO / WO3 composite material in gas sensing.
[0009] The technical solution adopted to achieve the purpose of the present invention is:
[0010] A WO3 snowflake-shaped nanoplate is prepared by the following steps:
[0011] K2C2O4·H2O, Na2WO4·2H2O and PVP were dissolved in water and dispersed evenly. HCl was then added to adjust the pH to 1.5-2. The mixture was kept at 110-130°C for 9-11 hours. The product was collected, washed and dried. The obtained solid powder was calcined at 370-420°C for 50-70 minutes to obtain WO3 snowflake-shaped nanoplates.
[0012] In the above technical solution, the mass ratio of K2C2O4·H2O, Na2WO4·2H2O and PVP is (4.5-5.5):(9.5-10.5):(0.8-1.2).
[0013] In the above technical solution, the side length of the nanoplate in the WO3 snowflake-shaped nanoplate is 300-600nm.
[0014] Another aspect of the present invention is a method for preparing a CuO / WO3 composite material, comprising the following steps:
[0015] The WO3 snowflake-shaped nanoplates and CuO nanoparticles are uniformly dispersed in water, and the mixture is kept at 160-180°C for 7-9 hours. The solid product is taken out and dried to obtain a CuO / WO3 composite material.
[0016] In the above technical solution, the method for preparing the CuO nanoparticles comprises the following steps:
[0017] Slowly adding NaOH solution to the aqueous solution of CuCl2 to adjust the pH value to 13.5-14, stirring to obtain a mixed solution, then adding ascorbic acid to the mixed solution and stirring again, collecting the product, washing and drying it, and calcining it at 320-370°C for 130-170 minutes to obtain the CuO nanoparticles.
[0018] Another aspect of the present invention also includes a CuO / WO3 composite material obtained by the preparation method.
[0019] In the above technical solution, the mass ratio of CuO in the CuO / WO3 composite material is 0.5% to 1.5%, preferably 1%.
[0020] In the above technical solution, the specific surface area of the CuO / WO3 composite material is 4.90-5.27m 2 / g, in the CuO / WO3 composite material, the particle size of the CuO nanoparticles is 600-900nm, and the side length of the WO3 snowflake-shaped nanoplate is 300-600nm.
[0021] Another aspect of the present invention also includes the use of the CuO / WO3 composite material in a gas sensor.
[0022] In the above technical solution, the gas is acetylacetone.
[0023] In the above technical solution, the operating temperature of the gas sensor is 260°C.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] 1. The present invention provides a novel method for synthesizing WO3 snowflake-shaped nanoplates. The snowflake-shaped WO3 nanoplates are assembled from many nanosheets, which may be attributed to the presence of surfactant PVP, which enables WO3 to grow in this special way.
[0026] 2. The present invention utilizes a simple hydrothermal method to prepare the CuO / WO3 composite material, which has low raw material cost and is conducive to large-scale production.
[0027] 3. The present invention provides for the first time a WO3-based nanomaterial for detecting acetylacetone gas, which has the characteristics of high sensitivity, high selectivity and stability, and rapid response and recovery.
[0028] 4. The composite material provided by the present invention achieves a response value of 73.1 to 100 ppm of acetylacetone at an operating temperature of 220°C. At an operating temperature of 260°C, the sensor's response to 100 ppm of acetylacetone gas reaches 49.3, and even at a low concentration of 1 ppm, it has a response value of 4.4. Notably, its response / recovery time is only 6 / 24 seconds, which is faster than existing acetylacetone sensors in terms of response and recovery, and it operates at a lower temperature, making it well suited for practical applications. Furthermore, the material exhibits excellent selectivity, cyclic stability, and long-term stability (>92 days). BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is the XRD pattern of WO3, CuO and CuO / WO3 composite material.
[0030] Figure 2 These are SEM images of (A) WO3, (B) CuO, (C) 0.5% CuO / WO3, (D) 1.0% CuO / WO3 and (E) 1.5% CuO / WO3.
[0031] Figure 3(A, B) TEM, (C) HRTEM images and (D) element distribution map of 1.0% CuO / WO3.
[0032] Figure 4 (A) O1s orbital and (B) W4f orbital XPS spectra of pure WO3 and 1.0% CuO / WO3. (C) Cu2p orbital XPS spectra of 1.0% CuO / WO3. (D) N2 adsorption-desorption isotherms of WO3 and its composites.
[0033] Figure 5 The graphs are (A) the relationship between the response value of pure WO3 and its composite material to 100 ppm acetylacetone and the operating temperature, and (B) the relationship between the response value at 260°C and the acetylacetone gas concentration.
[0034] Figure 6 This is the relationship between the response / recovery time and the operating temperature of the 1.0% CuO / WO3 sensor.
[0035] Figure 7 Dynamic response / recovery curves of (A) pure WO3 and (B) 1.0% CuO / WO3 sensors to 30 ppm acetylacetone gas at 260°C.
[0036] Figure 8 (A) Cyclic stability diagram of 1.0% CuO / WO3 sensor for 100 ppm acetylacetone gas at 260°C, (B) selectivity diagram of pure WO3 and composite material, and (C) long-term stability diagram. DETAILED DESCRIPTION
[0037] The present invention will be further described in detail below with reference to specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0038] Example 1
[0039] A WO3 snowflake-shaped nanoplate is prepared by the following steps:
[0040] (1) Dissolve 0.175 g K2C2O4·H2O, 0.335 g Na2WO4·2H2O, and 0.034 g PVP in 20 mL of high-purity water.
[0041] (2) After magnetic stirring for 30 min, 2 mL of HCl was added dropwise and magnetic stirring was continued for another 30 min.
[0042] (3) The solution was then transferred to a polytetrafluoroethylene-lined autoclave and kept in a drying oven at 120 °C for 10 h.
[0043] (4) The collected product was washed with high-purity water and anhydrous ethanol by centrifugation for more than three times, and then dried at 60°C overnight.
[0044] (5) The powder was calcined at 400 °C for 1 h with a heating rate of 2 °C / min.
[0045] Example 2
[0046] A method for preparing a CuO / WO3 composite material comprises the following steps:
[0047] Step 1, preparing WO3 snowflake-shaped nanoplates using the method of Example 1;
[0048] Step 2, preparation of CuO:
[0049] (1) Slowly add 100 mL of 2 mol / L NaOH to 50 mL of 0.1 mol / L CuCl2·2H2O and stir for 10 min to obtain a blue solution.
[0050] (2) Then, 50 mL of 0.1 mol / L ascorbic acid was added to the solution and stirred for 1 h.
[0051] (3) The product was collected and washed with high-purity water and anhydrous ethanol for more than three times by centrifugation, and then vacuum-dried at 60°C overnight.
[0052] (4) Calcination at 350°C for 150 min, with a heating rate of 2°C / min.
[0053] Step 3, preparation of CuO / WO3 composite material:
[0054] (1) Dissolve 200 mg of WO3 in 30 mL of high-purity water.
[0055] (2) Add 1 mg of CuO to the above solution and stir for 5 minutes.
[0056] (3) Then ultrasonicate for 30 minutes and stir for 5 minutes.
[0057] (4) The mixed solution was transferred to a polytetrafluoroethylene-lined autoclave and kept at 180 °C for 8 h.
[0058] (5) Finally, dry at 60°C overnight.
[0059] The CuO / WO3 composite material prepared in this example is recorded as 0.5% CuO / WO3 composite material.
[0060] Example 3
[0061] The preparation method of WO3 snowflake-shaped nanoplates and CuO in this embodiment is the same as that in Example 2.
[0062] The difference is step 3, preparation of CuO / WO3 composite material:
[0063] (1) Dissolve 200 mg of WO3 in 30 mL of high-purity water.
[0064] (2) Add 2 mg of CuO to the above solution and stir for 5 minutes.
[0065] (3) Then ultrasonicate for 30 minutes and stir for 5 minutes.
[0066] (4) The mixed solution was transferred to a polytetrafluoroethylene-lined autoclave and kept at 180 °C for 8 h.
[0067] (5) Finally, dry at 60°C overnight.
[0068] The CuO / WO3 composite material prepared in this example is recorded as 1.0% CuO / WO3 composite material.
[0069] Example 4
[0070] The preparation method of WO3 snowflake-shaped nanoplates and CuO in this embodiment is the same as that in Example 2.
[0071] The difference is step 3, preparation of CuO / WO3 composite material:
[0072] (1) Dissolve 200 mg of WO3 in 30 mL of high-purity water.
[0073] (2) Add 3 mg of CuO to the above solution and stir for 5 minutes.
[0074] (3) Then ultrasonicate for 30 minutes and stir for 5 minutes.
[0075] (4) The mixed solution was transferred to a polytetrafluoroethylene-lined autoclave and kept at 180 °C for 8 h.
[0076] (5) Finally, dry at 60°C overnight.
[0077] The CuO / WO3 composite material prepared in this example is recorded as 1.5% CuO / WO3 composite material.
[0078] The crystal phase and composition of WO3 were analyzed using a Rigaku Ultimate IV X-ray diffractometer (XRD) (manufactured by Rigaku, Japan) and a HORIBA EVOLUTION high-resolution laser confocal micro-Raman spectrometer (manufactured by HORIBA JOBINYVONS.AS). The microstructure of WO3 was analyzed using a Merlin Compact field emission scanning electron microscope (FESEM) (manufactured by Carl Zeiss AG) and a Talos F200X transmission electron microscope (TEM) (manufactured by Thermo Fisher Scientific). The chemical environment of the surface elements of the material was analyzed using an ESCALAB 250Xi X-ray photoelectron spectrometer (XPS) (manufactured by THERMOSCIENTIFIC). The specific surface area of WO3 was obtained using an ASAP2020 fully automatic specific surface area and pore physical adsorption analyzer (manufactured by Micromeritics Instruments (Shanghai) Co., Ltd.).
[0079] XRD was used to analyze the crystal phase and composition of WO3, CuO and CuO / WO3. Figure 1 As shown in A, it can be seen that the diffraction peaks are sharp and clear, indicating that the synthesized WO3, CuO and composite materials have high crystallinity. According to the standard card comparison (JCPDS: 72-0677), it can be seen that the WO3 synthesized by this method is a typical monoclinic phase with unit cell parameters of The diffraction peaks at 2θ angles of 23.1°, 23.6°, 24.3°, 26.6°, 28.6°, 28.9°, 41.4°, 41.9°, 47.2°, 48.2°, and 49.9° correspond to the (002), (020), (200), (120), (-112), (112), (-222), (222), (004), (040), and (400) planes of monoclinic WO3, respectively. In addition, according to the standard card reference (JCPDS: 80-0076), the synthesized CuO has a unit cell parameter of The CuO / WO3 composite material exhibits a monoclinic phase, with diffraction peaks at 2θ angles of 32.5°, 35.5°, 38.6°, 48.9°, 53.4°, 58.2°, and 61.5° corresponding to the (110), (-111), (111), (-202), (020), (202), and (-113) planes of the monoclinic CuO, respectively. The weak diffraction peak at 2θ angle of 35.5° in the CuO / WO3 composite material corresponds to the (-111) plane of CuO, and no other CuO diffraction peaks are found, which may be due to the small amount of CuO added. Figure 1Figure B amplifies the XRD pattern at 22°-25° 2θ. It can be seen that after pure WO3 is compounded with CuO, the diffraction peaks for the (002), (020), and (200) planes shift significantly. This is likely due to the strong interaction between WO3 and CuO in the composite material, demonstrating the successful formation of the CuO / WO3 heterojunction. Comparing pure WO3 with the composite material, it can be seen that the CuO compound has little effect on the crystallinity and crystalline phase of WO3. However, the crystallinity of the (002) plane of the CuO / WO3 composite material is much higher than that of other crystal planes, and its highly exposed surface may also contribute to the good selectivity of the gas sensor.
[0080] The morphology of the material was analyzed using SEM images. Figure 2 Figure A is the SEM image of pure WO3. It can be seen that WO3 snowflake-shaped nanoplates with relatively uniform dispersion and a side length of about 400nm were synthesized. Figure 2 B is the SEM image of CuO. It can be seen that CuO is a spherical material with a diameter of about 0.7 μm, but the dispersion is poor and many spheres are broken. Figure 2 The SEM images of DE of 0.5%, 1.0%, and 1.5% CuO / WO3 show that the addition of CuO did not significantly affect the morphology of WO3, but the size of the composite material was slightly larger than that of pure WO3, which may be attributed to the Ostwald ripening mechanism. The composite of CuO and WO3 was completed by hydrothermal method, and the additional hydrothermal step may cause the nanomaterial to continue to grow on the original basis. In addition, CuO dissolves from the original larger particles and re-grows into smaller nanoparticles (marked in red in the figure).
[0081] In order to observe the microstructure and element distribution of the composite material more intuitively, we used transmission electron microscopy to analyze it. Figure 3 In Figure A, we can see that the snowflake-shaped WO3 nanoplates are assembled from many nanosheets, which may be attributed to the presence of the surfactant PVP, which makes WO3 grow in this special way. Figure 3 In Figure B, clear morphologies of WO3 and CuO can be seen, with the red mark being the interface between the two phases, so a heterojunction may exist. Figure 3 The lattice spacing of 0.252nm and 0.365nm in C are respectively attributed to the (-111) plane of monoclinic CuO and the (200) plane of monoclinic WO3, and there is a clear phase interface between the two phases, confirming the existence of CuO / WO3 heterojunction. In addition, Figure 3 The element distribution map of D also confirms that Figure 3 The nanoparticles below B in the figure are CuO.
[0082] XPS was used to analyze the chemical composition and surface chemical state of pure WO3 and 1.0%CuO / WO3. Figure 4 A in the figure is the O1s spectrum of pure WO3 and 1.0% CuO / WO3, in which the Gaussian function peak at 530.3 eV is attributed to lattice oxygen, and the Gaussian function peak at 531.6 eV is attributed to chemically adsorbed oxygen. Figure 4 B is the W4f spectrum of pure WO3 and 1.0% CuO / WO3, where the Gaussian function peaks at 35.6eV, 37.7eV and 41.5eV correspond to the W4f 7 / 2 、W4f 5 / 2 and W5p 3 / 2 Comparing the two materials, it can be seen that after compounding with CuO, the three Gaussian function peaks of WO3 are all shifted to the high field by 0.1eV, indicating that after compounding with CuO, the electrons on WO3 flow to CuO, further demonstrating the successful formation of the CuO / WO3 heterojunction. Figure 4 The Cu2p fine spectrum of CuO / WO3 with 1.0% C, in which the Gaussian function peaks at 932.5eV and 952.3eV correspond to Cu2p respectively. 3 / 2 and Cu2p 1 / 2 , which shows that the Cu 2+ existence. Figure 4 D is the N2 adsorption-desorption isotherm of pure WO3 and three kinds of CuO / WO3 composite materials. It can be seen that all materials show type IV isotherms. The specific surface areas of pure WO3, 0.5% CuO / WO3, 1.0% CuO / WO3 and 1.5% CuO / WO3 are calculated by BET formula to be 5.80 m 2 / g, 4.90m 2 / g, 5.01m 2 / g and 5.27m 2 / g.
[0083] Example 5
[0084] This example uses the WO3 prepared in Example 1 and the CuO / WO3 composite materials prepared in Examples 2-4 as sensors for acetylacetone gas detection.
[0085] from Figure 5 It can be seen from Figure A that the response value of pure WO3 to 100ppm acetylacetone reaches its maximum at an operating temperature of 260℃, which is 22.1 (R a / R g), while the optimal operating temperature for the composite materials was 220°C. With increasing CuO concentration, the sensor response values increased to 63.5, 73.1, and 51.7, respectively. It is clear that the composite materials all had higher response values than pure WO3, with 1.0% CuO / WO3 exhibiting the highest response. At 220°C, the response of 1.0% CuO / WO3 to 100 ppm of acetylacetone gas increased by 4.1 times compared to pure WO3, and the operating temperature was reduced from 260°C to 220°C. Figure 5 Figure B shows the relationship between the response values of the four sensors and acetylacetone gas concentration at 260°C. It can be seen that the 1.0% CuO / WO3 composite still has a response value of 4.4 at an acetylacetone concentration of 1 ppm, indicating that the composite material has a low detection limit for acetylacetone gas and maintains high sensitivity even in the presence of low acetylacetone concentrations. Furthermore, it can be seen that the response values of the four sensors all follow a good logarithmic relationship with concentration, which is beneficial for practical application of the sensors.
[0086] like Figure 6 The response recovery time of the 1.0% CuO / WO3 sensor to 100ppm acetylacetone gas versus operating temperature curve shows that the sensor's response recovery time decreases with increasing operating temperature. At 220°C, the sensor's response / recovery time to 100ppm acetylacetone gas is 18 / 279s. A recovery time of 279s is difficult to meet practical production requirements for gas sensors, but increasing the operating temperature can effectively address this issue. It can be seen that the sensor's response and recovery times are significantly shortened from 220°C to 260°C. Further increasing the operating temperature after reaching 260°C does not significantly reduce the sensor's response and recovery times. At this temperature, the sensor's response / recovery time to 100ppm acetylacetone is 11 / 56s, and the sensor's response value reaches 49.3, which well meets the needs of practical applications. Therefore, 260°C is selected as the sensor's optimal operating temperature.
[0087] like Figure 7 Figures A and B are the dynamic response recovery curves of pure WO3 and 1.0% CuO / WO3 to 30ppm acetylacetone gas at 260°C. The response / recovery time of pure WO3 is 13 / 162s, while the response / recovery time of the sensor is reduced to 6 / 24s after being composited with CuO. The response and recovery times are shortened by 2.17 times and 6.75 times, respectively.
[0088] Cyclic stability and selectivity are very important performance indicators of gas sensors in practical applications. They determine the service life of the sensor and the accuracy of the response signal in complex atmospheres. Therefore, the cyclic stability and selectivity of the material were tested. Figure 8The 1.0% CuO / WO3 sensor shown in Figure A was subjected to 6 consecutive cycling stability tests at 260°C for 100ppm acetylacetone. It can be seen that the resistance of the sensor can basically return to its initial position at the end of each cycle, indicating that the sensor has good cycling stability. Figure 8 The selectivity test diagram of four sensors at 260°C shown in B is a graph, which tests 100ppm of acetylacetone and six other common reducing gases, namely NH3, acetone, ethanol, methanol, formaldehyde and n-hexane. It can be found that the response value of pure WO3 to 100ppm of acetylacetone vapor at 260°C is about 22.1, but it also has response values of 8.5 and 9.4 for NH3 and acetone. In practical applications, these interfering gases can easily cause serious errors to the working sensors. However, for 1.0% CuO / WO3, its response value to 100ppm of acetylacetone vapor reaches 49.3, but the response values for the other six gases are all below 6, so the CuO / WO3 composite material has good selectivity. Figure 1 In the XRD pattern mentioned above, we found that the proportion of (002) crystal plane of the composite material was significantly increased compared with pure WO3. The high (002) exposed surface of 1.0% CuO / WO3 may be the main reason for the good selectivity of the sensor for acetylacetone. The service life of the gas sensor is one of the most important performance indicators in practical applications. Figure 8 Figure C shows a 92-day intermittent test of a 1.0% CuO / WO3 sensor exposed to 100 ppm acetylacetone gas at 260°C. As can be seen, the sensor's response value showed almost no significant decrease after 92 days, demonstrating the excellent long-term stability of the CuO / WO3 composite sensor.
[0089] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A WO3 snowflake-shaped nanoplate, characterized in that: Prepared by the following steps: K2C2O4·H2O, Na2WO4·2H2O and PVP were dissolved in water and dispersed evenly. HCl was then added to adjust the pH to 1.5-2. The mixture was kept at 110-130°C for 9-11 hours. The product was collected, washed and dried. The obtained solid powder was calcined at 370-420°C for 50-70 minutes to obtain WO3 snowflake-shaped nanoplates.
2. The WO3 snowflake-shaped nanoplate according to claim 1, wherein: The mass ratio of K2C2O4·H2O, Na2WO4·2H2O and PVP is (4.5-5.5):(9.5-10.5):(0.8-1.2).
3. The WO3 snowflake-shaped nanoplate according to claim 1, wherein: The side length of the nanoplate in the WO3 snowflake-shaped nanoplate is 300-600nm.
4. A method for preparing a CuO / WO3 composite material, characterized in that: The following steps are involved: The WO3 snowflake-shaped nanoplates and CuO nanoparticles described in claim 1 are uniformly dispersed in water, kept warm at 160-180°C for 7-9 hours, and the solid product is taken out and dried to obtain a CuO / WO3 composite material.
5. The preparation method according to claim 4, wherein The preparation method of the CuO nanoparticles comprises the following steps: Slowly adding NaOH solution to the aqueous solution of CuCl2 to adjust the pH value to 13.5-14, stirring to obtain a mixed solution, then adding ascorbic acid to the mixed solution and stirring again, collecting the product, washing and drying it, and calcining it at 320-370°C for 130-170 minutes to obtain the CuO nanoparticles.
6. The CuO / WO3 composite material obtained by the preparation method as claimed in claim 4.
7. The CuO / WO3 composite material according to claim 6, wherein The mass ratio of CuO in the CuO / WO3 composite material is 0.5% to 1.5%, preferably 1%.
8. The CuO / WO3 composite material according to claim 6, wherein The specific surface area of the CuO / WO3 composite material is 4.90-5.27 m 2 / g, in the CuO / WO3 composite material, the particle size of the CuO nanoparticles is 600-900nm, and the side length of the WO3 snowflake-shaped nanoplate is 300-600nm.
9. Use of the CuO / WO3 composite material according to claim 6 in a gas sensor.
10. The use according to claim 9, characterized in that The gas is acetylacetone, and the operating temperature of the gas sensor is 260°C.